Building faith: the relationships between materials, form, and worship in pre-industrial religious architecture - Navdeep Kaur; Joseph Watts; Jamin Halberstadt (Current Research in Ecological and Social Psychology)
Religious structures have traditionally been seen as reflections of beliefs and practices, yet their design may also shape religious behavior and thought. This study investigates how local materials are related to the architecture and associated practices of pre-industrial religious structures, using data from the Database of Religious History (DRH) and additional coding of 121 sites. Results reveal that malleable materials like plaster and clay are linked to curved roofs, while wood is associated with larger structures. Larger buildings were more likely to support communal worship, whereas curved roofs were negatively associated with individual worship. Path analyses suggest that the relationship between materials and religious practices is accounted for by the architectural features, such as size and roof type, that those materials afford. Though correlational in nature, the findings illustrate a potential role of material constraints in shaping religious architecture and practices, as well as the embeddedness of religious life in its material and spatial context.